2019
DOI: 10.2147/ott.s215145
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-596 suppresses the expression of Survivin and enhances the sensitivity of osteosarcoma cells to the molecular targeting agent anlotinib</p>

Abstract: Background: Osteosarcoma (OSA), the most common primary bone malignancy, is characterized by a wide spectrum of complicated pathologies and frequent distal metastasis and causes death in adolescents and young adults worldwide. Antitumor drug treatment strategies include various cytotoxic chemotherapy drugs, while molecular targeted therapy for OSA is currently less used. The present work revealed the role played by the miR-596/Survivin axis in affecting the sensitivity of OSA cells to anlotinib, a novel molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Ma et al (31) reported that miR-6077 inhibited the expression of glucose transporter 1 and enhanced the anti-tumor effect of anlotinib on patient-derived lung adenocarcinoma cells. Another study indicated that miR-596 promoted the sensitivity of osteosarcoma to anlotinib by targeting survivin (32). Furthermore, Lu et al (33) revealed that supplementing exogenous C-X-C chemokine ligand 2 (CXCL2) may be a possible mechanism by which to circumvent anlotinib resistance.…”
Section: Preclinical Studies On Anlotinibmentioning
confidence: 99%
“…Ma et al (31) reported that miR-6077 inhibited the expression of glucose transporter 1 and enhanced the anti-tumor effect of anlotinib on patient-derived lung adenocarcinoma cells. Another study indicated that miR-596 promoted the sensitivity of osteosarcoma to anlotinib by targeting survivin (32). Furthermore, Lu et al (33) revealed that supplementing exogenous C-X-C chemokine ligand 2 (CXCL2) may be a possible mechanism by which to circumvent anlotinib resistance.…”
Section: Preclinical Studies On Anlotinibmentioning
confidence: 99%
“…In melanoma cells, elevated expression of miR-596 leads to enhanced cell apoptosis by targeting two apoptotic proteins [31]. Overexpression of miR-596 in osteosarcoma cells can promote the toxicity effect of anlotinib via the regulation of survivin [32]. Based on the tumor-suppressive role of miR-596 in gastric cancer [20], we first establish that circPRRX1 directly modulates miR-596 through a binding site.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal expression of miRNA is also closely related to the disease [ 36 , 37 ]. Of the three predicted miRNAs, MiR-658 is overexpressed in gastric cancer and induces gastric cancer metastasis by activating the PAX3-MET pathway [ 38 ], while miR-504 can inhibit cell proliferation and migration in non-small-cell lung cancer [ 39 ], oral squamous cell carcinoma [ 40 ], liver cancer [ 41 ], and overexpression in osteosarcoma [ 42 ], and breast cancer [ 43 ] to enhance the growth and metastasis of tumors.…”
Section: Discussionmentioning
confidence: 99%